2012
DOI: 10.1016/j.jjcc.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential target genes of cardioprotection against ischemia–reperfusion injury by express sequence tags analysis in rat hearts

Abstract: The global profiling of cardiac ischemia-related genes provides the possible mechanisms of IR and IPC and ways of treating IR injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
2
16
0
1
Order By: Relevance
“…Recently, a few in vitro studies have shown that TRAP1 overexpression protects isolated rat cardiomyocytes from hypoxia-induced mitochondrial damage and cell death [12,13]. In the present study, we found that TRAP1 overexpression also protects HL-1 cells, a cardiac muscle cell line, from hypoxic cell death.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Recently, a few in vitro studies have shown that TRAP1 overexpression protects isolated rat cardiomyocytes from hypoxia-induced mitochondrial damage and cell death [12,13]. In the present study, we found that TRAP1 overexpression also protects HL-1 cells, a cardiac muscle cell line, from hypoxic cell death.…”
Section: Discussionsupporting
confidence: 76%
“…Further, overexpression of TRAP1 in rat brain improves mitochondrial function and reduces focal ischemia-induced cerebral infarction and neurological impairments [12]. Other studies have found that TRAP1 expression is induced in rat hearts following I/R treatment in vivo [13] and in isolated rat cardiomyocytes following hypoxia treatment in vitro [14]. Further, TRAP1 overexpression prevents hypoxia-induced mitochondrial damage and cell death in isolated rat cardiomyocytes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Tu et al found that I/R induced rupture of myocardial fibers and degradation of F-actin as well as MLC-2 phosphorylation in the myocardial tissue [24]. Kim et al observed that I/R increased expression of genes encoding MLC-2 in rat hearts, which compensated for disorganization of sarcomeric myofibrillar proteins [29,30]. In this study, we found that H/R down-regulated MR-1 expression and induced disruption of F-actin and α-actinin disorganization with cardiomyocyte injury, as well as the up-regulation of MLC-2 expression and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Riskli miyokarttaki infarkt boyutunun küçülmesinde ve ST-segment elevasyonlu hastaların iyileştirilmesinde en etkili tedavi reperfüzyon terapisi olmasına rağmen, koroner kan akımının restorasyonunun paradoksal biçimde ek bir miyokart hasarını indükleyebilme ihtimali reperfüzyon terapisini iki ucu keskin bir bıçağa çevirmektedir 70 . Oksidatif stres, intraselüler kalsiyum birikimi, hızlı pH restorasyonu ve inflamasyon gibi birçok faktörün rol oynadığı kompleks bir olgu olan reperfüzyon hasarımitokondriyal geçirgenlik geçiş gözeneklerinin (MPTP, mitochondrial permeability transition pore) en azından kısmen açılmasına neden olur 71,72 .…”
Section: İskemi-reperfüzyon Hasarlarında Netrin-1unclassified